PERUMUSAN PREMI BULANAN ASURANSI KESEHATAN INDIVIDU PERAWATAN RUMAH SAKIT (ANUITAS HIDUP PEMBAYARAN BULANAN) - LAHALLO, AGUSTINA PAULA THERESIA PUTRI; WIDANA, I NYOMAN; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika, 2013)
This study calculates non renewable monthly premiums and renewable monthly premiums for health insurance. Formulations used in this study were derived from the equations used by Wilandari (2007). The monthly premium calculation  uses a CSO mortality table and an interest rate of 6%. To illustrate the calculating of the premium it is assumed that a family consist of a father, a mother and a son, respectively with age 40, 36 and 9 years old. The results obtained were that the  total premium is paid amounted to Rp. 155.02,00 every month for 20 years. Benefit for the cost of room, doctor visits, and the cost of care respectively were Rp. 200.000,00 per day, Rp. 75.000,00 per day and Rp. 4.000.000,00 per periode. Average duration of treatment was 180 days. The renewable  monthly premium was paid in different amounts each year, with the range from Rp. 80.425,00 to Rp. 406.465,00. From this study, Although initially the renewable premium is cheaper than the non renewable premium, at the end it is more expensive than the non renewable premium. In this study it was obtained too that 12 times the monthly premium  is greater than 1 times the annual premium.
Keywords: insurance; monthly payment; health insurance